Liver Metastasis Modulate Responses of Suppressive Macrophages and Exhausted T Cells to Immunotherapy Revealed by Single Cell Sequencing. Issue 4 (11th October 2022) - Zhang, Qiming; Liu, Siyuan; Liu, Yedan; Bhatt, Dev; Estrada, Juan; Belmontes, Brian; Ren, Xianwen; Canon, Jude; Ouyang, Wenjun
Abstract: Liver metastasis is associated with immunotherapy resistance, although the underlying mechanisms remain incompletely understood. By applying single cell RNA‐sequencing to a concurrent subcutaneous and liver tumor murine model to recapitulate liver metastases, it is identified that subsets within tumor‐infiltrating exhausted CD8 + T (Tex) cells and immunosuppressive tumor‐associated macrophages (TAMs) display opposite responses to concurrent liver tumors and anti‐PD‐1 treatment, suggesting a complex immune regulating network. Both angiogenic and interferon‐reactive TAMs show increased frequencies in implanted liver tumors, and anti‐PD‐1 treatment further elevates the frequencies of angiogenic TAMs. Such TAMs frequencies negatively correlate with the proportions of cytotoxic T cell subsets. Further, expression of interferon‐stimulated genes in TAMs is dramatically reduced under effective anti‐PD‐1 treatment, while such tendencies are diminished in mice with implanted liver tumors. Therefore, the study indicates that liver metastases could increase immunosuppressive TAMs frequencies and inhibit Tex responses to PD‐1 blockade, resulting in compromised systemic antitumor immunity and limited immunotherapy efficacy. Abstract : By applying single cell RNA‐sequencing to a concurrent subcutaneous and liver tumor murine model to recapitulate liver metastases, tumor‐infiltrating exhausted CD8 + T (Tex) cells, immunosuppressive tumor‐associated macrophages, and interferon‐stimulated gene scores are identified to display opposite responses to liver metastasis and anti‐PD‐1 treatment, suggesting a complex immune regulating network.